Can a School Operational Assistance Fund Program (BOS) Reduce School Drop-Outs During The Post-Rising Fuel Prices In Indonesia? Evidence From Indonesia - Bayu Kharisma (Muhammadiyah University Press, 2018)
This study aims to analyze the impact of school operational assistance fund program (BOS program) on the dropout rate during the post-rising fuel prices using Indonesian Family Life Survey (IFLS) and difference in difference approach. The results showed that the impact of BOS on the dropout rate of students aged 7-15 years during the period investigated in this study was lower than those who did not receive BOS fund, but it was not statistically significant. In the meantime, if the account of the research is to be limited to the influenc e of students aged 16-20 years who had previously received the benefit of BOS, it shows that BOS program had a positive influence to the dropout rates. However, children aged 16-20 years who had not previously received benefits BOS negatively affect the dropout rates. Based on this fact, the benefit of the BOS following the fuel price hike in Indonesia during the research period did not seem to be particularly effective in lowering the dropout rate.